Effects of Bedaquiline on Antimicrobial Activity and Cytokine Secretion of Macrophages Infected with Multidrug-Resistant Mycobacterium tuberculosis Strains. (11th April 2022) - Lyu, Xia-Li; Lin, Ting-Ting; Gao, Jing-Tao; Jia, Hong-Yan; Zhu, Chuan-Zhi; Li, Zi-Hui; Dong, Jing; Sun, Qi; Shu, Wei; Wang, Sai-Sai; Pan, Li-Ping; Huang, Hai-Rong; et al.
Abstract : Background . Bedaquiline (Bdq) exerts bactericidal effects against drug-susceptible and drug-resistant Mycobacterium tuberculosis strains, including multidrug-resistant M. tuberculosis strains (MDR-MTBs). However, few reported investigations exist regarding Bdq effects on MDR-MTBs-infected macrophages activities and cytokine secretion. Here, Bdq bactericidal activities against MDR-MTBs and related cellular immune mechanisms were explored. Methods . Macrophages infected with MDR-MTBs or H37Rv received Bdq treatments (4 h/8 h/24 h/48 h) at 1 × the minimum inhibitory concentration (1 × MIC), 10 × MIC and 20 × MIC. Intracellular colony-forming units (CFUs) and culture supernatant IL-12/23 p40, TNF- α, IL-6, and IL-10 were determined using the Luminex® 200 TM system. Normally distributed continuous data (mean ± standard deviation) were analyzed using t- test or F -test (SPSS 25.0, P < 0.05 deemed statistically significant). Results . (1) 100% of Bdq-treated macrophages (all doses applied over 4–48 h) survived with 0% inhibition of proliferation observed. (2) Intracellular CFUs of Bdq-treated MDR-MTBs-infected macrophages decreased over 4–48 h of treatment, were lower than preadministration and control CFUs, decreased with increasing Bdq dose, and resembled H37Rv-infected group CFUs (48 h). (3) For MDR-MTBs-infected macrophages (various Bdq doses), IL-12/23 p40 levels resembled preadministration group levels and exceeded controls (4 h); TNF- α levels exceeded preadministration group levels (24 h/48 h) and controls (24 h); IL-12/23 p40 and TNF- α levels resembled H37Rv-infected group levels (4 h/8 h/24 h/48 h); IL-6 levels exceeded preadministration and H37Rv-infected group levels (24 h/48 h) and controls (24 h); IL-10 levels resembled preadministration and H37Rv-infected group levels (4 h/8 h/24 h/48 h) and were lower than controls (24 h/48 h); IL-12/23 p40 and IL-10 levels remained unchanged as intracellular CFUs changed, with IL-12/23 p40 levels exceeding controls (4 h) and IL-10 levels remaining lower than controls (24 h/48 h); TNF- α and IL-6 levels increased as intracellular CFUs decreased (24 h/48 h) and exceed controls (24 h). Conclusion . Bdq was strongly bactericidal against intracellular MDR-MTBs and H37Rv in a time-dependent, concentration-dependent manner. Bdq potentially exerted immunomodulatory effects by inducing high-level Th1 cytokine expression (IL-12/23 p40, TNF- α ) and low-level Th2 cytokine expression (IL-10).